Transforming growth factor‐β, matrix metalloproteinases, and urokinase‐type plasminogen activator interaction in the cancer epithelial to mesenchymal transition. Issue 3 (24th August 2017) - Santibanez, Juan F.; Obradović, Hristina; Kukolj, Tamara; Krstić, Jelena
Abstract : Transforming growth factor‐β (TGF‐β) is a pleiotropic factor that acts as a tumor suppressor in the early stages, while it exerts tumor promoting activities in advanced stages of cancer development. One of the hallmarks of cancer progression is the capacity of cancer cells to migrate and invade surrounding tissues with subsequent metastasis to different organs. Matrix metalloproteinases (MMPs) together with urokinase‐type plasminogen activator (uPA) and its receptor (uPAR), whose main original function described is the proteolytic degradation of the extracellular matrix, play key cellular roles in the enhancement of cell malignancy during cancer progression. TGF‐β tightly regulates the expression of several MMPs and uPA/uPAR in cancer cells, which in return can participate in TGF‐β activation, thus contributing to tumor malignancy. TGF‐β is one of the master factors in the induction of cancer‐associated epithelial to mesenchymal transition (EMT), and recently both MMPs and uPA/uPAR have also been shown to be implicated in the cancer‐associated EMT process. In this review, we analyze the main molecular mechanisms underlying MMPs and uPA/uPAR regulation by TGF‐β, as well as their mutual implication in the development of EMT in cancer cells. Developmental Dynamics 247:382–395, 2018 . © 2017 Wiley Periodicals, Inc. Key Findings: Increasing number of evidence supporting the important role of the TGF‐β, MMPs and uPA/uPAR system in the way of tumor progression and metastasis ‐TGF‐β regulates both MMPs and uPA expression in cancer cells, while MMPs and uPA may activate the latent secreted TGF‐β, thus producing a pernicious cycle which contributes to the enhancement of tumor progression. TGF‐β, MMPs and uPA/uPAR contribute to the cancer EMT induction, which enhances tumor cells migration and invasion. The complex interplay and roles of TGF‐β, MMPs and uPA/uPAR in cancer is critical and the understanding of their participation in the initiation, progression and tumor metastasis could eventually reveal potential combinations targeting with the current oncotherapies.